2019
DOI: 10.1002/job.2399
|View full text |Cite
|
Sign up to set email alerts
|

The indirect relations of workplace incivility with emotional exhaustion and supportive behaviors via self‐blame: The moderating roles of observed incivility and trait emotional control

Abstract: Summary Drawing from the social cognitive theory of self‐regulation, we develop a model linking experienced incivility to emotional exhaustion and supportive behaviors via self‐blame, with observed incivility experienced by coworkers as a first‐stage moderator and trait emotional control as a second‐stage moderator. We contend that employees will experience self‐blame if they perceive themselves to be distinct targets of incivility (i.e., observed incivility experienced by others is low). Self‐blame can potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 88 publications
(194 reference statements)
0
31
0
Order By: Relevance
“…The current study shows that there is a positive impact of perceived organizational politics on emotional exhaustion. Moreover, Workplace incivility significantly affects emotional exhaustion (Alola et al, 2020;Hur et al, 2016;Karatepe et al, 2019;Peng et al, 2016;Rahim & Cosby, 2016;Tong et al, 2019). The mediation adds novelty for this study as workplace incivility was a mediator of perceived organizational politics on emotional exhaustion.…”
Section: Discussion Of Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The current study shows that there is a positive impact of perceived organizational politics on emotional exhaustion. Moreover, Workplace incivility significantly affects emotional exhaustion (Alola et al, 2020;Hur et al, 2016;Karatepe et al, 2019;Peng et al, 2016;Rahim & Cosby, 2016;Tong et al, 2019). The mediation adds novelty for this study as workplace incivility was a mediator of perceived organizational politics on emotional exhaustion.…”
Section: Discussion Of Resultsmentioning
confidence: 73%
“…A study conducted by Makhdoom et al (2017) expounded that there is a significant impact of perceived organizational politics on the workplace incivility of high school teachers at private and government schools. Furthermore, there were previous studies conducted and investigated that workplace incivility significantly affects emotional exhaustion (Alola et al, 2020;Hur et al, 2016;Karatepe et al, 2019;Peng et al, 2016;Rahim & Cosby, 2016;Tong et al, 2019). However, there is a lack of studies on this area in the apparel sector.…”
Section: Perceived Organizational Politics Workplace Incivility and Emotional Exhaustionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is especially stronger for those employees who tend to be high in neuroticism vis-à-vis those who are low in neuroticism. Also noteworthy to the purpose of the current study was an investigation focusing on police officers in China, which drew on the social cognitive theory of self‐regulation (Tong et al , 2019). Findings identified that experienced incivility may generate supportive behaviors from targets by means of self‐blame.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It can be the starting point in fostering more oppressive forms of aggression in organizations [12]. However, few studies have empirically examined the role of observers, despite their positive role in reacting to manifestations of and intervening in incivility [13][14][15][16] rather than blaming the victim or doing nothing [17]. To date, we still do not know what makes observers detect and react to uncivil behaviors.…”
Section: Introductionmentioning
confidence: 99%